Can we improve the diagnosis of renal failure? A revised coding system for the Middle East and North Africa - Guy H Neild; D Deren Oygar; Mohamed Ben Hmida (Saudi Journal of Kidney Diseases and Transplantation, 2011)
We reviewed the regional data on primary renal disease (PRD) causing end-stage renal failure (ESRF) during the decade 2000-2009. Reporting was generally inconsistent and diagnostic groups were poorly defined. We propose a system in which all diagnoses fall into one of eight broad groups: ESRF of uncertain etiology, congenital abnormalities of the kidney and urinary tract (CAKUT) and acquired uropathy, glomerular diseases, tubulo-interstitial disease (TID), other congenital and familial diseases, diabetes, renovascular disease and other specified diagnoses. Each group has sub-headings; for instance, primary glomerulonephritis, secondary glomerulonephritis, and hereditary glomerular disease. For each sub-heading, there is a list of specific diagnoses similar to that used by the European Dialysis and Transplant Association (EDTA) and United States Renal Data System (USRDS) coding systems. We also recommend that "etiology unknown" group should be reported in more detail as either "glomerular phenotype" or "tubular phenotype" and careful attention be paid to evidence for a family history of renal disease. To improve reporting, all patients who are diabetic, and all who have evidence of familial inheritance, should be recorded and a diagnostic category should be chosen. Thus, a diabetic patient is designated as "diabetic nephropathy" only if he/she fulfils the case definition for that diagnosis. We believe that the collection can be done much better as exemplified by the pediatric community, where data collection is very consistent, and there is a low rate of "unknown disease".